2007
DOI: 10.1096/fj.06-7938com
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of matrix metalloproteinase‐2 (MMP‐2) activity by phosphorylation

Abstract: The regulation of matrix metalloproteinases (MMP) has been studied extensively due to the fundamental roles these zinc-endopeptidases play in diverse physiological and pathological processes. However, phosphorylation has not previously been considered as a potential modulator of MMP activity. The ubiquitously expressed MMP-2 contains 29 potential phosphorylation sites. Mass spectrometry reveals that at least five of these sites are phosphorylated in hrMMP-2 expressed in mammalian cells. Treatment of HT1080 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 33 publications
5
123
0
2
Order By: Relevance
“…The same results were obtained when PKC-δ was down regulated by siRNA (Fig 3.A and B). The data are consistent with other showing that MMP-2 is modulated by phosphorylation and that PKC may be, in vivo, a regulator of this protease [28], PKC-δ included [29]. Indeed, we found that in response to cisPt administration a subsequent PKC-δ activation occurred after as soon as 15 min (Fig 3.C).…”
Section: Discussionsupporting
confidence: 93%
“…The same results were obtained when PKC-δ was down regulated by siRNA (Fig 3.A and B). The data are consistent with other showing that MMP-2 is modulated by phosphorylation and that PKC may be, in vivo, a regulator of this protease [28], PKC-δ included [29]. Indeed, we found that in response to cisPt administration a subsequent PKC-δ activation occurred after as soon as 15 min (Fig 3.C).…”
Section: Discussionsupporting
confidence: 93%
“…3A, right). Human MMP-2 contains 29 potential phosphorylation sites, and some of them are phosphorylated by PKC (31). Thus, we examined the phosphorylation status of MMP-2 in the conditioned medium of transfected COS-1 cells treated with or without PMA by Western blotting with antibodies against phosphothreonine and phosphoserine.…”
Section: Mmp-2 Forms Amentioning
confidence: 99%
“…Metalloproteinase activation can result from oxidative stress [19,20], post-translational modifications such as phosphorylation [21] and protein-protein interactions [22,23].…”
Section: Nonproteolytic Mechanismsmentioning
confidence: 99%
“…Cardiac PKC may modulate intracellular MMP-2 activity by phosphorylation at multiple sites including Ser and Thr residues. Indeed, mammalian MMP-2 contains 29 potential phosphorylation sites and mass spectrometry reveals that at least five of these sites are phosphorylated [21]. The kinase activity of extracellular signal-regulated kinase, ERK, leads to phosphorylation of the Thr 735 of ADAM-17/TACE rendering ADAM-17 able to shed tumor necrosis factor (TNF)-α [29].…”
Section: Nonproteolytic Mechanismsmentioning
confidence: 99%